DEFICIT IRRIGATION EFFECTS ON WATERMELON (CITRULLUS VULGARIS) IN A SUB HUMID ENVIRONMENT - H. Kuşçu; A. Turhan; N. Özmen; P. Aydınol; H. Büyükcangaz; A. O. Demir (Journal of Animal and Plant Sciences, 2015)
In sub-humid environments where summer drought is intense, the efficient use of water is important for sustainable crop production. Watermelon has high water requirements. The application of deficit irrigation (DI) strategies to this crop may greatly contribute to save irrigation water. A two-year study was conducted with the aim to evaluate the effects of DI on water productivity, yield and some quality properties of watermelon in a sub-humid environment in western Turkey. Five irrigation treatments [FI-Full, DI1-deficit=100% and 50% crop evapotranspiration (ETc) restoration during whole growing season, respectively; DI2= 100% ETc up to flowering, then 50% ETc restoration; DI3=100% ETc up to yield formation, then 50% ETc restoration; DI4= 100% ETc up to ripening stage, then 50% ETc restoration] were arranged in randomized complete block design with 3 replications in both experimental years. The maximum marketable fruit yield was determined from full irrigation level. Results showed that marketable yield significantly decreased by reduction in irrigation. In spite of the yield loses up to averagely 31% under DI1 conditions, saved 50% of water as compared to treatment of full irrigation. The highest values of total soluble solids and total sugar were found in treatments of DI1 and DI2. Higher values of vitamin C and lycopene were observed in DI3 treatment. Water productivity was positively affected by reduction in irrigation. Yield response factor (ky), which indicates the level of tolerance of a crop to water stress, was 1.01 for marketable yield, indicating that the reduction in crop productivity is proportionally equal to the relative ET deficit. The study revealed that the best compromise among water productivity, quantity and quality for watermelon was achieved with DI4 that 100% ETc up to ripening, then 50% ETc restoration.
Keywords: Watermelon; Water stress; Water use efficiency; Yield; Antioxidants